Validation of the Single Assessment Numeric Evaluation (SANE) Score as an Outcome Measure by Comparison to the Revised Foot Function Index (rFFI). Issue 3 (9th August 2019) - Bellas, Nicholas; Cirino, Carl; Cote, Mark P.; Sathe, Vinayak; Geaney, Lauren
Background: Patient-reported outcome measures serve as an invaluable tool in both the clinical and research setting to monitor a patient's condition and efficacy of treatments over time. We aim to validate the Single Assessment Numeric Evaluation (SANE) score for disorders of the lower extremity using the revised–Foot Function Index (rFFI) as a reference. The SANE score is a 1-question survey that may improve efficiency of outcome data collection in the clinical setting. Methods: Patient age, sex, visit diagnosis by ICD-10 code, SANE score, and rFFI score were collected retrospectively from 218 initial patient encounters between January 2015 through July 2017. Patients were included if they were 18 years or older and were excluded if they had incomplete SANE or rFFI data. Results of the two scores were compared using the Pearson or Spearman correlation coefficients, with correlation defined as excellent (>0.7), excellent-good (0.61-0.7), good (0.4-0.6), or poor (0.2-0.39). Diagnoses were categorized into 9 subgroups that were analyzed, including forefoot, plantar fasciitis, arthritis, deformity, fracture, tendinitis, osteochondral defect (OCD) of the talus, acute soft tissue trauma, and "other." Results: The SANE score had good correlation with the overall rFFI score ( r = 0.51, P < .01). When comparing the SANE score to the rFFI subscores, there was good correlation with pain ( r = 0.42, P < .01), good correlation with stiffness ( r = 0.44, P < .01), poor correlation with activity ( r = 0.36, P <.01), good correlation with difficulty ( r = 0.52, P < .01), and poor correlation with social issues ( r = 0.39, P < .01). Subanalysis showed an excellent-good correlation between SANE and rFFI score for forefoot pathology ( r = 0.67, P < .01) and plantar fasciitis ( r = 0.63, P < .02), good correlation for arthritis ( r = 0.49, P < .04), deformity ( r = 0.60, P < .01), fracture ( r = 0.50, P < .01), and tendinitis ( r = 0.47, P < .02), and no significant correlation for OCD of the talus ( r = 0.56, P < .15) and acute soft tissue trauma ( r = 0.19, P < .32). Conclusion: The SANE score demonstrates excellent-good correlation with the rFFI for specific pathology including the forefoot and plantar fasciitis and has limited correlation with other pathology.